IMPLEMENTASI UNDANG-UNDANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (TINJAUAN SOSIOLOGIS TERHADAP KULTUR BUDAYA DALAM KOMUNITAS JAWA) - ., Dewi Gunawati dan Moh. Muchtarom (PKn Progresif, 2006)
Legalized decree No. 23/ 2004 about house hold violence abolition is an important moment where the law principle to protect victim in the private area had been a cover to protect and look after their right. The Javanese people are not only socially and culturely strong to keep after the women position against men?s domination. It surely must use special approach to implement. The drcree so that value friction from the effect of this decree application don?t give the conflict in the society.